Shell variability in Tawera gayi (Veneridae) from southern SouthAmerica: A morphometric approach based on contour analysis - Gordillo, Sandra (2011)
This study analyses the significance of shell morphological variations in the venerid clam Tawera gayi, a typical element of shallow marine soft bottoms in southern South America and the most common species recovered from Late Quaternary marine deposits along the Beagle Channel, Tierra del Fuego. Fossil and modern Tawera shells from different localities around the southern tip of South America were analysed using the Elliptic Fourier Analysis (EFA) method. Taking into account the palaeontological history of this genus in the southern hemisphere, EFA was also performed on shells of Tawera congeners from South Africa (T. philomela) and New Zealand (T. spissa). The use of EFA permitted the distinction between the three Tawera species and geographical differentiation in the T. gayi groups. These morphological variations of T. gayi appear best related to ecophenotypic plasticity as a response to different environmental conditions, although the palaeobiogeographical history of Tawera in South America cannot be ruled out.